2018
DOI: 10.1002/suco.201700276
|View full text |Cite
|
Sign up to set email alerts
|

Seismic reliability evaluation of tunnel form (box‐type) RC structures under the accidental torsion

Abstract: In the tunnel form (box‐type) structural system, walls arrangement and mass distribution have important effect on the interactions of thinner shear walls and slab configurations. In the other words, despite the regularity of these buildings as well as symmetry in wall arrangement and mass distribution, the first mode of structural behavior in many cases is twisting. This characteristic is limited to the flexible torsional buildings, which are often sensitive to the mass eccentricity and rotational components o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Several studies have been also performed on the effects of accidental torsions due to eccentricities of centers of mass, strength, or stiffness, on the seismic performance of tunnel-form building structures (Mohsenian and Mortezaei, 2018; Mohsenian et al, 2018, 2021a; Mortezaei and Mohsenian, 2022). In general, the outcomes of these studies indicate that the accidental torsions have no significant influence on the performance level of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been also performed on the effects of accidental torsions due to eccentricities of centers of mass, strength, or stiffness, on the seismic performance of tunnel-form building structures (Mohsenian and Mortezaei, 2018; Mohsenian et al, 2018, 2021a; Mortezaei and Mohsenian, 2022). In general, the outcomes of these studies indicate that the accidental torsions have no significant influence on the performance level of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…The reinforcing contribution of steel fibers can be mobilized in planar SFRC elements, such as elevated SFRC slabs, as the primary reinforcement 29 . Many studies conducted, in recent years, on the specifications and characteristics of fiber reinforced concrete, including the effects of volume, aspect ratio, geometry, alignment and resistance of fibers 30–44 . Most studies have been focused on concrete technology and structural components such as beams, columns and connections.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the forward directivity can influence the failure modes of tall tunnel-form structures and reduce the reliability of the design. Mohsenian and Mortezaei (2018a) also evaluated the seismic reliability of tunnel-form structures subjected to accidental torsions. According to their results, eccentricity of mass centre by up to 10% of the plan dimension does not considerably affect the performance of these systems.…”
Section: Introductionmentioning
confidence: 99%